Strategi Efektif Pengendalian Internal dalam Keamanan Sistem Informasi Akuntansi untuk Perlindungan Data Keuangan - Andini Kartika Dewi; Berliana Kristiananova Sibarani; Edi Saputra; Norazlina Norazlina; Sri Susanti; Yunda Syafira; Yarzan munakalla (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Accounting Information Systems (AIS) play a crucial role in managing an organization's financial data. However, challenges such as hacking threats, unauthorized access, and human errors can jeopardize the security and integrity of financial data. Therefore, effective internal control is required to ensure the reliability of financial information. This study aims to analyze effective internal control strategies to enhance AIS security and protect financial data from both external and internal threats. This research employs a qualitative descriptive approach through a literature review of various scientific journals, books, and official publications. The content analysis technique is used to identify patterns and strategies in AIS internal control. The findings indicate that effective internal control strategies include employee training, data encryption, two-factor authentication, periodic system monitoring, and proper system integration. Additionally, routine audits and a culture of compliance within the organization contribute to enhancing financial data security. Strong internal control in AIS can improve the security and reliability of financial information. The implementation of security technologies and employee awareness of data protection are key factors in preventing information breaches. Companies should continuously update internal control policies, enhance technological infrastructure, and conduct regular employee training to improve the effectiveness of accounting information systems in addressing evolving security challenges.